Effect of IAA Addition and Some Organic Supplements on Growth and Rooting of Cavendish Banana (Musa Acuminata, AAA) In-Vitro - Riza Intikhatus Sholikhah; Makhziah Makhziah; Widiwurjani Widiwurjani (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2022)
In vitro propagation of Cavendish banana is an alternative to produce healthy, uniform and sufficient plant materials of high qualities. Appropriate culture media formulation is needed for shoot growth and rooting stage. This experiment aimed to study effects of IAA and organic supplements on in vitro shoot growth and rooting. Explants were subjected to MS medium with IAA and various organic supplements, in a factorial arrangement of a completely randomized design. The first factor was IAA concentrations (0; 0.5; 1 and 1.5 mg.L-1), and the second factor was types of organic supplement (control, coconut water, potato extract and banana extract). At 8 weeks after planting, shoot growth and root performance of plantlets were recorded. The results showed that addition of IAA did not affect shoot height. Addition of potato extract and banana homogenate resulted in the highest plantlets. Medium with IAA at 1 mg.L-1 resulted in the highest number of roots. The highest number of shoots was produced on media with IAA 1 mg.L-1 + coconut water and IAA 1.5 mg.L-1 + potato extract. The highest number of roots was produced in medium with potato extract. The longest roots were produced in media with 0.5 mg.L-1 IAA + banana homogenate. Keywords: Banana extract, Cavendish, Coconut water, IAA, Potato extract